2011
DOI: 10.1002/ijc.26322
|View full text |Cite
|
Sign up to set email alerts
|

Molecular history of Richter syndrome: origin from a cell already present at the time of chronic lymphocytic leukemia diagnosis

Abstract: Richter syndrome (RS) represents the transformation of chronic lymphocytic leukemia to aggressive lymphoma. We explored intraclonal diversification (ID) of immunoglobulin genes in order to (i) follow the evolutionary history of the RS clone (ii) compare the role of ID in clonally related RS vs. clonally unrelated cases. Most (10/11, 90.9%) clonally related RS stem from the predominant clone observed at CLL diagnosis. One single RS had a transformation pattern compatible with sequential evolution from a seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…RS is usually manifested by disease transformation into diffuse large B-cell lymphoma, which is often refractory to treatment and carries a poor prognosis. Most RS cases are clonally related to the pre-existing CLL, with TP53 disruption being one of the most frequent underlying genomic alterations2526. Clinically, the diagnosis of RS is often not straightforward and relies on a high index of clinical suspicion and accurate tissue biopsy.…”
Section: Resultsmentioning
confidence: 99%
“…RS is usually manifested by disease transformation into diffuse large B-cell lymphoma, which is often refractory to treatment and carries a poor prognosis. Most RS cases are clonally related to the pre-existing CLL, with TP53 disruption being one of the most frequent underlying genomic alterations2526. Clinically, the diagnosis of RS is often not straightforward and relies on a high index of clinical suspicion and accurate tissue biopsy.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 20% of cases are unrelated to the CLL clone and are considered as second cancer arising in a patient with CLL. [ 52 ] The incidence of RT ranges from 2 to less than 10%. [ 44,53-55 ] The influence of prior treatment especially with purine analogues on the incidence of RT is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Since immunogenetic investigations have shown that the subclone from which RS emerges is already identifiable at CLL diagnosis in most patients who subsequently develop RS (114), deep sequencing studies performed in sequential samples are needed to assess whether traces of the genetic lesions manifestly acquired at RS transformation are already present at CLL diag-nosis. Preliminary evidence suggests that this might be the case, at least in some patients (45).…”
Section: Pathways To Richter Transformationmentioning
confidence: 99%